2022
DOI: 10.1609/aaai.v36i5.20410
|View full text |Cite
|
Sign up to set email alerts
|

Almost Full EFX Exists for Four Agents

Abstract: The existence of EFX allocations of goods is a major open problem in fair division, even for additive valuations. The current state of the art is that no setting where EFX allocations are impossible is known, and yet, existence results are known only for very restricted settings, such as: (i) agents with identical valuations, (ii) 2 agents, and (iii) 3 agents with additive valuations. It is also known that EFX exists if one can leave n-1 items unallocated, where n is the number of agents. We develop new tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…ere are, however, positive results for any number of agents if the valuation functions are restricted [6,38,29], if it is allowed to discard some of the goods [19,22,23,12], or if one considers approximate EFX allocations [5]. Finally, regarding the notion of MMS, allocations that provide this guarantee always exist when there are only 2 agents, although computing them is an NP-hard problem [46].…”
Section: Further Related Workmentioning
confidence: 99%
“…ere are, however, positive results for any number of agents if the valuation functions are restricted [6,38,29], if it is allowed to discard some of the goods [19,22,23,12], or if one considers approximate EFX allocations [5]. Finally, regarding the notion of MMS, allocations that provide this guarantee always exist when there are only 2 agents, although computing them is an NP-hard problem [46].…”
Section: Further Related Workmentioning
confidence: 99%
“…Chaudhury et al [2021c] presented an algorithm that computes a partial EFX allocation, but the number of unallocated goods is at most n−1, and no agent prefers the set of these goods to her own bundle. e la er result was recently improved by Berger et al [2022] who showed that the unallocated goods can be decreased to n − 2 in general, and to just one for the case of four agents. Finally, Chaudhury et al [2021b] showed that a (1 − ε)-EFX allocation with a sublinear number of unallocated goods and high Nash welfare can be computed in polynomial time for every constant ǫ ∈ (0, 0.5].…”
Section: Relaxations Of Efxmentioning
confidence: 99%
“…Although the additivity of the valuation functions is considered a standard assumption, there are many works that explore richer classes of valuation functions. Some prominent examples include the computation of EF1 allocations for agents with general non-decreasing valuation functions [28], EFX allocations (or relaxations of EFX) under agents with cancelable valuation functions [12,1,19] and subaditive valuation functions [33,20], respectively, and approximate MMS allocations for submodular, XOS, and subadditive agents [11,23].…”
Section: Further Related Workmentioning
confidence: 99%
“…Although the stability and equilibrium fairness properties of Round-Robin have been visited before [8,5], to the best of our knowledge, we are the first to study the problem for non-additive valuation functions and go beyond exact pure Nash equilibria. Cancelable functions also generalize budget-additive, unit-demand, and multiplicative valuation functions [12], and recently have been of interest in the fair division literature as several results can be extended to this class [12,1,19]. For similar reasons, cancelable functions seem to be a good pairing with Round-Robin as well, at least in the algorithmic setting (see, e.g., Proposition 2.5).…”
Section: Introductionmentioning
confidence: 97%